Economic of underdevelopment : a series of articles and papers selected and edited by A. N. Agarwala and S. P. Singh - "Agarwala, A N (ed)." (London, 1971)
This book cover the following topics: Approaches of the problem of underdevelopment; The historical context; The Theoretical context; External economics and balanced growth;Underemployment and factor- disequilibrium;Models of development etc.